A new instrument prototype to measure the geometric surface area of nanoparticles with a time resolution of 1s. (June 2019) - Su, Lipeng; Ou, Qisheng; Cao, Leo N.Y.; Du, Qian; Pui, David Y.H.
Abstract: The first online method with 1s time resolution for Geometric Surface Area (GSA) measurement of aerosol nanoparticles and the corresponding instrumentation prototype were proposed and developed in this study. This developed method consists of one diffusion charger, followed by two electrostatic precipitators (ESPs) and two electrometers to acquire two current signals simultaneously, from which GSA concentration is determined by a weighed sum method, with a time resolution of 1s. The method and prototype were first calibrated and verified with monodisperse particles, and its sensitivities under different high voltages were then studied to seek an optimal linear combination between two current signals. Finally, the developed method was tested by both solid and liquid polydisperse nanoparticles and was compared with the Scanning Mobility Particle Sizer (SMPS). The results showed that this developed method can successfully measure the GSA concentration of aerosol nanoparticles with a good accuracy. The largest difference between this method and SMPS is less than 8%. Highlights: A new instrument prototype was proposed to measure the GSA concentration of nanoparticles with a 1s time resolution. Developed method was validated by polydisperse particles and compared with SMPS to verify its advantages. Developed prototype has a great potential to be applied for nanoparticle GSA measurement in commercial fields.